Notes on Mycetia (Rubiaceae) - O. G. Gideon; S. S. Tjitrosoedirdjo; J. F. Veldkamp (PTTI, 1997)
Account of the 3 species in Cibodas, Java; M. fasciculata is not aheterostylous form of M. cauliflora; lectotype specimens of M. fasciculata and M. javanica are indicated